2023
DOI: 10.1161/circulationaha.122.057987
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Outcomes Among Pregnant Women With Congenital Heart Disease–Associated Pulmonary Hypertension

Abstract: Background: Studies focused on pregnant women with congenital heart disease (CHD)–associated pulmonary hypertension (PH) are scarce and limited by small sample sizes and single-center design. This study sought to describe the pregnancy outcomes in women with CHD with and without PH. Methods: Outcomes for pregnant women with CHD were evaluated retrospectively from 1993 to 2016 and prospectively from 2017 to 2019 from 7 tertiary hospitals. PH was diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…They found that compared with the mild and moderate groups, the mean gestational week, age of the pregnancy, and NYHA cardiac functional classification grade in the severe PAH group were dramatically different. The incidence of pregnancy‐related complications in the severe PAH group was significantly higher than those in the mild and moderate PAH groups 20,21 …”
Section: Discussionmentioning
confidence: 97%
“…They found that compared with the mild and moderate groups, the mean gestational week, age of the pregnancy, and NYHA cardiac functional classification grade in the severe PAH group were dramatically different. The incidence of pregnancy‐related complications in the severe PAH group was significantly higher than those in the mild and moderate PAH groups 20,21 …”
Section: Discussionmentioning
confidence: 97%
“…Prior to the advent of prostacyclin as a medication for PAH, pregnant patients with PAH had higher rates of mortality (30 -56%) and fetal death (11 -28%). 32,34 With the development of PAH-specific treatments, however, there have been improvements in maternal and fetal mortality rates, 32,34,41,42 with more reports of successful pregnancy outcomes. Several small studies have reported maternal mortality rates of 16% to 17%.…”
Section: Discussionmentioning
confidence: 99%
“…Several small studies have reported maternal mortality rates of 16% to 17%. 38,[41][42][43] One study of seven pregnant women reported that patients treated for PAH prior to pregnancy had less RV dysfunction compared with newly diagnosed patients who had never received PAH treatment. 38 Another study of 2,200 patients focused on pregnant women with congenital heart disease, with and without PH.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 5 show increasing numbers of women with CHD and PH with completed pregnancy over the study years, along with improved outcomes. Although this population overall remains at very high risk, variability in risk was seen within the PH subgroup, with a higher risk of adverse events for women with higher estimated pulmonary pressures, more advanced functional class, and higher BNP levels.…”
Section: Article See P 549mentioning
confidence: 98%
“…In this issue of Circulation , Zhang et al 5 report on pregnancy and postpartum outcomes for women at 7 referral centers in China, including 2200 women with congenital heart disease (CHD), 729 of whom had probable PH. This cohort is remarkable for its large size, including more women with PH than several previous meta-analyses.…”
mentioning
confidence: 99%